Demystifying student plagiarism in academic writing: Towards an ‘educational’ solution - Ndebele, Hloniphani (Critical Studies in Teaching and Learning, 2023)
Plagiarism has become a recurrent challenge in higher education institutions, threatening the integrity of universities and their academic standards. The exacerbation of this issue can be largely linked to the escalating presence of online resources, which are easily accessible to knowledge and information communities worldwide. Many universities have thus instituted reactive measures that focus on detecting and policing plagiarism with little consideration of proactive and educational measures that can address the primary reasons for plagiarism and foster a community of academic integrity on their campuses. The purpose of this paper is, therefore, to interrogate the treatment of plagiarism in universities, and provide recommendations for better educational approaches to address this issue in proactive ways that also acknowledge the complex, contextual background of the South African higher education landscape. Understanding the primary reasons students plagiarise is critical in finding educational rather than punitive solutions to address the issue.